List of Reviewers 2016 - Lis, Piotr (Research Papers in Economics and Finance, 2017)
CZYŻEWSKI Bazyli, Poznań University of Economics and Business, Poland GRABOWSKI Grzegorz, Poznań University of Economics and Business, Poland JARNO Klaudia, Poznań University of Economics and Business, Poland KVILINSKYI Oleksii, National Economy of Sciences of Ukraine, Ukraine KWIATKIEWICZ Piotr, Military University of Technology MAZURKIEWICZ Joanna, Poznań University of Economics and Business, Poland MUTASCU Mihai, West University of Timisoara, Romania NIZIOŁ Krystyna, University of Szczecin PIĄTEK Dawid, Poznań University of Economics and Business, Poland POPOVA Olga, Donetsk National Technical University (Pokrovsk), Ukraine SAPA Agnieszka, Poznań University of Economics and Business, Poland SZCZERBOWSKI Radosław, Poznan University of Technology ZWIERZCHLEWSKI Sławomir, Poznań University of Economics and Business, Poland